2018
DOI: 10.1530/eje-18-0237
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and follow-up of type 2 diabetes in women with PCOS: a role for OGTT?

Abstract: Polycystic ovary syndrome (PCOS) is common in premenopausal women. The majority of women with PCOS have insulin resistance and the risk of type 2 diabetes mellitus (T2D) is higher in women with PCOS compared to controls. In non-pregnant women with PCOS, glycemic status may be assessed by oral glucose tolerance test (OGTT), fasting plasma glucose (FPG) or HbA1c. OGTT has been reckoned gold standard test for diagnosing T2D, but OGTT is rarely used for diagnostic purpose in other non-pregnant individuals at risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 102 publications
(159 reference statements)
3
27
0
2
Order By: Relevance
“…PCOS is a stronger risk factor for stroke than a family history of CVD (odds ratio: 1.38, 95% CI 1.01 to 1.88) ( Valerio et al , 2016 ). Given the increase in cardiometabolic risk, it is understandable that cardiometabolic screening of women with PCOS is regularly suggested in international guidelines ( Huang and Coviello, 2012 ; Andersen and Glintborg, 2018 ). However, it is important to consider that increased risk alone does not justify screening ( Andermann et al , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is a stronger risk factor for stroke than a family history of CVD (odds ratio: 1.38, 95% CI 1.01 to 1.88) ( Valerio et al , 2016 ). Given the increase in cardiometabolic risk, it is understandable that cardiometabolic screening of women with PCOS is regularly suggested in international guidelines ( Huang and Coviello, 2012 ; Andersen and Glintborg, 2018 ). However, it is important to consider that increased risk alone does not justify screening ( Andermann et al , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the FPG and A1c tests, numerous investigations show that the OGTT is the best single measure for predicting subsequent diabetes, disease, and/or mortality [ 17 , 18 , 19 , 20 , 21 ]. Although more time-consuming and difficult to administer for the diagnosis of diabetes, the OGTT is considered by many to be the gold standard [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Consequently, in the present study, the OGTT was used as the referent in each comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Although there remains uncertainty about the role of HbA1c in women with PCOS, to test for prediabetes and T2DM, the ADA stated that FPG, 75g OGTT and HbA1c are equally appropriate, including women with PCOS 18 . Furthermore, some studies suggested that in women with PCOS, HbA1c might be a good indicator or may be applied instead of OGTT in most instances 26,27 . Thus, our study has the merit of using both HbA1c and OGTT.…”
Section: Discussionmentioning
confidence: 92%